Social Contagion in Bullying: an Examination of Strains and Types of Bullying Victimization in Peer Networks - Stubbs-Richardson, Megan (American journal of criminal justice, 2021)
This study examined risk and protective factors for four types of bullying victimization – physical, verbal, relational, and cyber bullying – while assessing the influence of vicarious, anticipated, and experienced strains from General Strain Theory. In this study, experienced strain was operationalized as exposure to negative stimuli, such as rejection. Vicarious strain was operationalized as witnessing or being aware of other people’s negative experiences, such as peer victimization, and anticipated strain occurred when an individual had negative expectations about the future, such as a fear of harm. Using a sample of Southeastern high school students, this study found that individuals who experienced vicarious strain (peer victimization) had a higher likelihood of experiencing the same type of victimization as their peers. Previous bullies were also likely to experience the same type of bullying that they initiated. Anticipated strain (fear of attack) was associated with an increased likelihood of experiencing verbal and cyber bullying. Adult support was associated with an increased likelihood of verbal bullying but decreased likelihood of relational bullying victimization. Peer support was associated with an increased likelihood of experiencing relational and cyber bullying victimization. The results support Agnew’s ( 2006 ) proposal that experienced, vicarious, and anticipated strains are correlated with antisocial behavior and victimization (Zavala & Spohn, 2013 ). Policy implications and directions for future research are discussed.